Accountability Analysis in the Implementation of Employees Performance in Kanreg II BKN Surabaya - Wahyuni, Sri; Aliyaturrahma, Ikadona (Advances in Social Sciences Research Journal, 2019)
The research aims to analyze administrative and professional accountability in the implementation of employees performance in Kanreg II BKN Surabaya. There are two elements in the implementation of employees performance, namely Employee Work Targets and Work Behavior. Antonio Bar Cendon (1999), states that there are four forms of accountability typology, namely a) Political Accountability b) Administrative Accountability c) Professional Accountability d) Accountability for Democracy. The research uses descriptive qualitative method that focuses on operational principle, internal accountability, external accountability, subject matter, criteria, mechanism, and consequences. Data collection technique is done by observation, interviews, and documentation. The results of the analysis of administrative and professional accountability in implementing employees performance in Kanreg II BKN Surabaya are more dominant type of administrative and professional accountability, that can be seen from the sub-indicator of the dominant type of administrative accountability. The research is inseparable from the supporting factors, namely regulation, supervision, application systems, description of main tasks and functions, rewards, and sanctions.